Applicability of the parenting workshop in the Mineiro Judicial Power: A descriptive and spatial analysis - Loreto , Maria das Dôres Saraiva de; Raposo , Katia Roberta Portes Silva (Seven Editora, 2023)
In this article, we sought to analyze the applicability of the parenting workshop in the Judiciary of the State of Minas Gerais, through a quali-quantitative approach, considering its characteristics and spatialization. To complement the analysis, by means of a case study, together with the CEJUSC workshops, in the District of Viçosa-MG, a scan was carried out in the Center's database and the questionnaires applied to the participants, at the end of the workshops, by the exhibitors were analyzed. The sample consisted of 74 respondents, who participated in workshops held between 2018 and 2019. The data were processed and analyzed using the GNU PSPP software, resulting in tabular and graphical analyses. The data obtained in field research with the Districts of Minas Gerais were projected on a georeferencing map, through the free software QGis 3.2.1, aiming at a spatial analysis of the object of study. As a result, it was found that, although the parenting workshop was implemented in Brazil in 2014, its application in the Court of Justice of Minas Gerais is still limited. In addition, although, in the perception of the public involved, the workshops held in the District of Viçosa-MG proved to be effective in resolving family conflicts, strategies are needed to expand the scope of the instrument and more empirical studies on this topic are needed. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-141